1966
DOI: 10.6028/jres.070a.012
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra of the hydrated borates

Abstract: Infrare d absorption spectra of 42 diffe rent hydrated borates were obtained in the 2000-300 em -I range. A few spec tra were obtained between 4000 a nd 2000 em-I. Most spectra are complex and cannot be interpreted sati sfactorily except in the case of the simp lest an ions. Many correlatIOns be twee n spectra are possible, however, and possible anion types have been deduced. Differentiation be twee n triangular a nd tetrah e dral boron is possible on th e basis of th e spectra but IS less certain than in th e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 11 publications
4
48
0
Order By: Relevance
“…The two weak bands at 1628 cm À 1 are related to the bending of -NH 2 . The strong bands at 1410, 1321 and 929 cm À 1 are the asymmetric and symmetric stretching modes of B-O in BO 3 , while the bands at 1135, 1062, 1021, and 779 cm À 1 are characteristic of the asymmetric and symmetric stretching modes of B-O in BO 4 [49][50][51], and the stretching vibrations of the C-N band are also located around 1062 cm À 1 . The band at 1200 cm À 1 is related to the in-plane bending mode of B-O-H group.…”
Section: Infrared (Ir) Spectramentioning
confidence: 99%
“…The two weak bands at 1628 cm À 1 are related to the bending of -NH 2 . The strong bands at 1410, 1321 and 929 cm À 1 are the asymmetric and symmetric stretching modes of B-O in BO 3 , while the bands at 1135, 1062, 1021, and 779 cm À 1 are characteristic of the asymmetric and symmetric stretching modes of B-O in BO 4 [49][50][51], and the stretching vibrations of the C-N band are also located around 1062 cm À 1 . The band at 1200 cm À 1 is related to the in-plane bending mode of B-O-H group.…”
Section: Infrared (Ir) Spectramentioning
confidence: 99%
“…Spectra were obtained on (010) cleavage fragments// c and// a with a Perkin Elmer 180 spectrometer ( fig. 1) (Moenke, 1974;Weir and Schroeder, 1964;Weir, 1966). Absorption due to B0 4 groups lies in the 1180 to 800 em -1 region.…”
mentioning
confidence: 99%
“…While several infrared studies of colemanite have been reported on powdered samples (Weir 1966;Weir and Schroeder 1964;Plyusnina and Kharitonov 1963;Vlasova and Valyashko 1966;Valyashko and Wlassowa 1969) and one on single crystals (Burnel and Vierne 1970), we present the first polarized infrared and far infrared single crystal study of this mineral, including spectra of the low temperature ferroelectric phase.…”
Section: Introductionmentioning
confidence: 99%